CHLORIDE PENETRATION ON GROUND NUT SHELL ASH CONCRETE UNDER ACIDIC ENVIRONMENT - K, PANDI.; K, GANESAN. (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Groundnut shell ash is one of the important pozzolanic materials containing that can be mixed with ordinary Portland cement for the manufactured of long durable and good valuable product. The present experimental evaluation is rapid chloride permeability test (RCPT). The effect of hydrochloric acid (HCL) on properties of replaced ground nut shell ash concrete is taken as research area. However at 20% replacement level of ground nutshell ash more resistance to 3% Hydrochloric acid attack.